TINDAKAN SAMPLING PADA KARYA CIPTA MUSIK DALAM PERSPEKTIF UNDANG–UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Galih Wahyu Wicaksono (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article was conducted to find out the views on sampling action in terms of Law No. 28 of 2014 concerning Copyright and to find out how legal protection can be carried out by an Author or Copyright Holder. Sampling is an act of taking or using a part of the copyrighted work of an Author or Copyright Holder which will later be used in a new composition. The method in this research uses empirical writing methods and uses a qualitative approach. The results of the research show that sampling is not an infringement of Copyright if it is not carried out for commercial activities where commercial activities have violated the economic rights of the Creator or the Copyright Holder, if the objective is for commercial activities then it must obtain permission from the Creator or Copyright Holder, Creator or Holder. Copyright can enter into a license contract to protect his copyrighted works and has the right to file a lawsuit for compensation if his rights have been violated and caused losses, and there are criminal provisions to protect works belonging to the Creator or the Copyright Holder. In addition, the Creator or Copyright Holder can register a work, this is done as an initial presumption to prove copyright ownership, but it cannot be used as absolute evidence.Keywords: Copyright; Sampling; Music; Economic Rights